2006
DOI: 10.1097/01.mlg.0000216807.03225.ce
|View full text |Cite
|
Sign up to set email alerts
|

Safety Study of the Cochlear Nucleus® 24 Device with Internal Magnet in the 1.5 Tesla Magnetic Resonance Imaging Scanner

Abstract: Use of the 1.5 Tesla MRI on subjects with Cochlear Nucleus 24 implants did not result in any significant demagnetization of the internal magnet and did not cause displacement of the magnet when an external compression dressing was applied. Surgical removal of the internal magnet before scanning with the 1.5 Tesla MRI may not be necessary if a compression dressing is applied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
55
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(58 citation statements)
references
References 10 publications
2
55
0
1
Order By: Relevance
“…Although there is a risk that the magnet may become displaced from the device, this did not occur when it was bound in cadavers (10). Displacement of the magnet has been described in an MRI with binding, although in this case the patient had a previous procedure to remove and replace the magnet, which may have weakened the pocket (15).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Although there is a risk that the magnet may become displaced from the device, this did not occur when it was bound in cadavers (10). Displacement of the magnet has been described in an MRI with binding, although in this case the patient had a previous procedure to remove and replace the magnet, which may have weakened the pocket (15).…”
Section: Discussionmentioning
confidence: 95%
“…Cadaver studies have shown that the force required to fracture the CI receiver bed was much higher than that generated in a 1.5-T MRI scanner (7,8). Although demagnetization of the internal magnet is a concern, in practice this effect has been minimal even after multiple MR images (5,9,10), and the effect probably is only significant with 3-T scanners (11).…”
mentioning
confidence: 95%
“…8,13,19,24 Buna karşın bazı çalışmalarda ise MRG'nin implanta herhangi bir zarar vermediği belirtilmektedir. [52][53][54][55][56] Böyle bir durum karşısında kohlear implant cerrahisi geçiren hastanın implantı takan cerraha danışması uygun olacaktır. 8 Kohlear implantın dış parçasının sudan sakınılması gerektiği konusunda hasta ve yakınları bilgilendirilir.…”
Section: Taburculuk Eği̇ti̇mi̇unclassified
“…CI manufacturers have developed devices with removable magnets, and several articles have addressed the issues related to the MRI compatibility and safety of CIs [1,2] . Gubbels et al [1] conducted a cadaveric study and found that performing a 1.5-Tesla MRI on subjects with Cochlear Nucleus 24 implants did not result in any significant demagnetization of the internal magnet, nor was there any displacement of the magnet when an external compression dressing was applied. They concluded that surgical removal of the internal magnet before scanning with the 1.5-Tesla MRI may not be necessary if a compression dressing is applied.…”
Section: Introductionmentioning
confidence: 99%